2019
DOI: 10.3390/molecules24061137
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in Crotonaldehyde-Induced Endothelial Toxicity

Abstract: Crotonaldehyde is an extremely toxic α,β-unsaturated aldehyde found in cigarette smoke, and it causes inflammation and vascular dysfunction. Autophagy has been reported to play a key role in the pathogenesis of vascular diseases. However, the precise mechanism underlying the role of acute exposure crotonaldehyde in vascular disease development remains unclear. In the present study, we aimed to investigate the effect of crotonaldehyde-induced autophagy in endothelial cells. Acute exposure to crotonaldehyde decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…These indicators strongly suggest that CRA is associated with arterial dysfunction and structural changes in the vasculature. One study confirmed that acute exposure to high concentrations of CRA induces arterial dysfunction and structural changes in the vasculature through activated MAPK pathways [ 45 ]. Meanwhile, we confirmed that the activation of MAPK pathways can directly induce structural changes and arterial dysfunction in the vasculature with low concentrations of CRA (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…These indicators strongly suggest that CRA is associated with arterial dysfunction and structural changes in the vasculature. One study confirmed that acute exposure to high concentrations of CRA induces arterial dysfunction and structural changes in the vasculature through activated MAPK pathways [ 45 ]. Meanwhile, we confirmed that the activation of MAPK pathways can directly induce structural changes and arterial dysfunction in the vasculature with low concentrations of CRA (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Autophagy, a cellular process involving lysosome-mediated degradation, is pivotal for protein breakdown, cytoplasmic organelle renewal, and recycling of cellular components [ 80 ]. Four functions of autophagy, cytoprotective, nonprotective, cytotoxic, and cytostatic, have been reported in the existing literature [ 81 ].…”
Section: Molecular Regulatory Mechanisms Of Tumor Dormancymentioning
confidence: 99%